Synbiotic Musa acuminata skin extract and Streptococcus salivarius K12 inhibit candida species biofilm formation. Issue 6 (3rd July 2022) - Rismayuddin, Nurul Alia Risma; Mohd Badri, Puteri Elysa Alia; Ismail, Ahmad Faisal; Othman, Noratikah; Bandara, H.M.H.N.; Arzmi, Mohd Hafiz
Abstract: This study aimed to determine the effect of synbiotic Musa acuminata skin extract (MASE) and Streptococcus salivarius K12 (K12) on Candida species biofilm formation. Liquid chromatography quadrupole time-of-flight (LC-Q-TOF-MS) was conducted to characterize MASE. To determine the effect of synbiotic on Candida biofilm, 200 µL of RPMI-1640 containing Candida, K12, and MASE were pipetted into the same well and incubated at 37 °C for 72 h. A similar protocol was repeated with K12 or MASE to determine the probiotic and prebiotic effects, respectively. Dimorphism, biofilm biomass, and Candida total cell count (TCC) were determined. A total of 60 compounds were detected in MASE. C. albicans (ALT5) and Candida lusitaniae exhibited the highest reduction in biofilm biomass when co-cultured with prebiotic (77.70 ± 7.67%) and synbiotic (97.73 ± 0.28%), respectively. All Candida spp. had decreased TCC and hyphae when co-cultured with synbiotic. In conclusion, MASE and K12 inhibit Candida biofilm formation.